Teachers’ Expectation and Acceptance of a Home-grown Networked Automated Essay Scorer with Feedback (AESF) for the Malaysian University English Test (MUET) Classroom - Ng, Sing Yii; Hong, Kian Sam; Lee, Nung Kion; Bong, Chih How (2015)
In the process of introducing any system into the classroom context, the teachers’ acceptance and expectation are the prerequisite for its success because teachers are the ones who implement the system. They are the driving forces that ensure the system takes place, works and serves its purposes. This study aimed at determining teachers’ acceptance and expectation on the introduction of an automated networked-based essay scorer that provides immediate feedback in terms of score and remarks as a whole and even at the paragraph level called the Automated Essay Scoring Feedback (AESF). A total of eight experienced MUET teachers were selected to be interviewed. The qualitative findings were analysed, coded and trended. The findings indicates that essay writing is the most underdeveloped skills. It is very demanding on the students and is definitely the most laborious task for the teachers who guide, assess, respond and document their student’s writing. The proposal of a home-grown and networked AESF was positively accepted by the teachers despite some who were unsure about its ability in mimicking human raters and other possible concerns such as the lack of computer resources, technical support and proper training for teachers and students. The findings of this study provided some practical considerations towards the design and development of AESF that include the need for immediacy, ease of use, usefulness, reliability and validity. The AESF is an innovative solution that assist the most challenging language teachers’ task; essay marking. Being home-grown, AESF can overcome a fundamental drawback of commercially available Automated Essay Scorer (AES), namely cultural-sensitivity and validity.